Предмет: Алгебра,
автор: olesea2000
корень из 6 - корень из 3 - корень из 2 + 1 делить на корень из 10 - корень из 5 + корень из 2 - 1. Упростить выражение. Простите, что словами
Ответы
Автор ответа:
0
(√6-√3-√2+1)/(√10-√5+√2-1)=[√3(√2-1)-(√2-1)]/[√5(√2-1)+(√2-1)]=
=(√2-1)(√3-1)/(√2-1)(√5+1)=(√3-1)(√5-1)/[(√5+1)(√5-1)]=
=(√3-1)(√5-1)/(5-1)=(√3-1)(√5-1)/4
=(√2-1)(√3-1)/(√2-1)(√5+1)=(√3-1)(√5-1)/[(√5+1)(√5-1)]=
=(√3-1)(√5-1)/(5-1)=(√3-1)(√5-1)/4
Похожие вопросы
Предмет: Алгебра,
автор: nastyha227
Предмет: Алгебра,
автор: yanaolenyuk334
Предмет: Математика,
автор: pilotfhn
Предмет: История,
автор: КристинаСR7
Предмет: Математика,
автор: gogo270903